2012
DOI: 10.5897/ajb12.2092
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of Ethiopian indigenous goat populations

Abstract: A survey was conducted to study the morphological characteristics of indigenous goats in representative zones and districts of Amhara Region of Ethiopia as a first step towards characterization and designing of breeding programs. A pre-tested questionnaire was used for recording morphological features, body weights and linear body measurements. Both qualitative and quantitative traits were recorded on 158 goats randomly sampled from six goat populations and the data were analyzed using GenStat version 13 softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 16 publications
(12 reference statements)
9
54
7
3
Order By: Relevance
“…, TadlaouiOuafai et al 62 , and lower than that reported by Oliviera et al 42 , Hassen et al 47 , Li et al 48 , Gour et al 51 , Dixit et al 63 and Kumar et al 64 . Luikart et al 1 and Naderi et al 3 have stated that a lower F ST value generally observed in goat populations results from a higher mobility of goats between different regions, which reduces a genetic differentiation between populations.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…, TadlaouiOuafai et al 62 , and lower than that reported by Oliviera et al 42 , Hassen et al 47 , Li et al 48 , Gour et al 51 , Dixit et al 63 and Kumar et al 64 . Luikart et al 1 and Naderi et al 3 have stated that a lower F ST value generally observed in goat populations results from a higher mobility of goats between different regions, which reduces a genetic differentiation between populations.…”
contrasting
confidence: 52%
“…, Hassen et al 47 and Li et al 48 . The mean number of alleles/locus/breed found in this study (between 10.33 and 11.33) were similar to those found by Bozkaya et al 49 , Korkmaz-Ağaoğlu and Ertuğrul 50 and higher than those reported by Behl et al 35 , Saitbekova et al 38 , Agha et al 39 , Barker et al 45 , Li et al 48 , Gour et al 51 , Jandurova et al…”
mentioning
confidence: 99%
“…Heart girth explains about 80.4 to 93.6 % total variation in live body weight in Indian goat breed of Kanni Adu kids under farmer's management system. Live body weight is significantly correlated to heart girth (r=0.899) and to body length (r=0.729) for Gumuz, Begia-Medir and Agew goat ecotypes of the Amhara region of Ethiopia [11]. More recent finding for Abergelle goat breed emphasized that body weight has relatively high relationship with heart girth (0.73-0.89) as compared with the other body measurements, body length (0.46-0.82) and height at wither (0.53-0.83) [8].…”
Section: Application Of Lbm For Estimation Of Live Body Weightmentioning
confidence: 99%
“…Currently, there are different research works done on indigenous goats which can contribute for designing of improvement programs. Most of the researches done were focused on issues like characterization of production systems [4], physical description [5], molecular genetic characterization [6] and health [7] of different breeds. But studies on the growth performance of kids particularly for Bati, Borana and Short-eared Somali goat populations are scarce and poorly documented.…”
Section: Introductionmentioning
confidence: 99%